KUALITAS AUDIT DAN KARAKTERISTIK KOMPETENSI AUDITOR - Made Edy Septian Santosa; Putu Riska Wulandari (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
Audit quality is a possibility that an auditor will find and report violations in his client's accounting system. This study was conducted to examine the influence of auditor competency characteristics (independence, integrity, accountability, experience, understanding of the client industry, responsiveness to client needs) on audit quality in the Public Accounting Firm in Bali. Data analysis used in this study is a research instrument test and multiple linear regression techniques. The results of the study are expected to be able to understand the relevance of the characteristics of auditor competence to the audit quality of the Public Accountant Office. In addition, KAP can consider various competency characteristics of auditors in improving the quality of auditor work to achieve good audit quality.